The Acquis Communautaire within TTIP - The Case of Romania - Ioana Gutu (CES Working Papers, 2015)
On every enlargement, European Union applies to all its new Member States a set of common legal norms, known under the name of acquis communautaire, norms that also include multilateral or bilateral international agreements the EU is part of. Currently, the EU and the US are negotiating a regional trade agreement, namely the Transatlantic Trade and Investment Partnership (TTIP), of which effects over the Member States will be established according to their particular national legal order, as part of the EU acquis, presented under the form of secondary EU legislation. As part of the 28 EU Member States, Romania's legal system will apply the European international norms that regard the dispute resolutions that might occur among states or states and investors, in accordance with the European's Court of Justice (ECJ) jurisprudence, as it will be provided by the legal text of TTIP, after it will be adopted, ratified and implemented by the EU, and subsequently, by each of the European Union's Member States.
Keywords: F13; 330; acquis communautaire; TTIP; EU law